2017
DOI: 10.1002/jsfa.8464
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of ochratoxin A from raw black tea to tea infusions prepared according to the Turkish tradition

Abstract: BACKGROUND: Ochratoxin A (OTA) is a natural contaminant of food including tea with multiple toxic effects, which poses a threat to human health. In terms of lifestyle, the Turkish population is a frequent visitor of tearooms, and the traditional Turkish tea preparation is one of the most popular ways of preparing tea infusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 33 publications
(36 reference statements)
2
10
0
Order By: Relevance
“…Few studies were focused on tea brew analysis for the reason of mycotoxin transfer estimation [ 16 , 39 , 46 ] or analytical method development [ 35 , 38 , 60 ]. Mycotoxin extraction from brewing was carried out by means of IAC (ochratoxin A targeted analysis) [ 28 , 39 ] or dispersive liquid-liquid microextraction (16 mycotoxins, recovery from 66% to 127%) [ 38 ] or liquid-liquid extraction and “dilute and shoot” approach (proved to be suitable for ochratoxin A detection) [ 60 ].…”
Section: Methods Of Mycotoxin Determination In Teamentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies were focused on tea brew analysis for the reason of mycotoxin transfer estimation [ 16 , 39 , 46 ] or analytical method development [ 35 , 38 , 60 ]. Mycotoxin extraction from brewing was carried out by means of IAC (ochratoxin A targeted analysis) [ 28 , 39 ] or dispersive liquid-liquid microextraction (16 mycotoxins, recovery from 66% to 127%) [ 38 ] or liquid-liquid extraction and “dilute and shoot” approach (proved to be suitable for ochratoxin A detection) [ 60 ].…”
Section: Methods Of Mycotoxin Determination In Teamentioning
confidence: 99%
“…Mycotoxin extraction from brewing was carried out by means of IAC (ochratoxin A targeted analysis) [ 28 , 39 ] or dispersive liquid-liquid microextraction (16 mycotoxins, recovery from 66% to 127%) [ 38 ] or liquid-liquid extraction and “dilute and shoot” approach (proved to be suitable for ochratoxin A detection) [ 60 ]. Hence, the authors followed their preference while preparing tea brew, in short, 1.5–2 g of ground raw tea sample was put in contact with 150–250 mL of boiling water for 3–8 min [ 16 , 35 , 38 , 39 ] or Turkish traditional brewing [ 46 ]; it is reasonable to propose standard procedure [ 60 , 63 ].…”
Section: Methods Of Mycotoxin Determination In Teamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of commercial black and green teas based on routine laboratory analyses using high-performance liquid chromatography (HPLC) with tandem mass spectrometry (MS/MS) and fluorescence detectors (FLD) indicated high rates of storage-related mycotoxins, such as aflatoxins (AFs) and ochratoxin A (OTA), which were found in dry tea leaves and into their infusions [8][9][10]. Mannani et al (2020) reported that more than half of all tested green tea samples (59%, n = 76) from a Moroccan tea market were positive for aflatoxin B 1 (AFB 1 ) and other AFs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of commercial black and green teas based on routine laboratory analyses using high-performance liquid chromatography (HPLC) with tandem mass spectrometry (MS/MS) and fluorescence detectors (FLD) indicated high rates of storage-related mycotoxins, such as aflatoxins (AFs) and ochratoxin A (OTA), which were found in dry tea leaves and into their infusions [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%